2016
DOI: 10.1515/popore-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

New records of crustose Teloschistaceae (lichens, Ascomycota) from the Murmansk region of Russia

Abstract: Twenty-three species of crustose Teloschistaceae were collected from the northwest of the Murmansk region of Russia during field trips in 2013 and 2015. Blastenia scabrosa is a new combination supported by molecular data. Blastenia scabrosa, Caloplaca fuscorufa and Flavoplaca havaasii are new to Russia. Blastenia scabrosa is also new to the Caucasus Mts and Sweden. Detailed morphological measurements of the Russian specimens of these species are provided. Caloplaca exsecuta, C. grimmiae and C. sorocarpa are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Geography : Although described from a single locality in Svalbard (Søchting et al, ), it has since been found in Hrubý Jeseník Mountains in the Czech Republic (Vondrák et al, ; Vondrák & Malíček, ), Tatra Mountains in Poland (Wilk, ), Caucasus Mountains in Abkhasia, Murmansk region in Russia, Torne Lappmark in Sweden (Frolov & Konoreva, ) and here it is newly reported from Sierra Nevada in Spain.…”
Section: Taxonomymentioning
confidence: 65%
“…Geography : Although described from a single locality in Svalbard (Søchting et al, ), it has since been found in Hrubý Jeseník Mountains in the Czech Republic (Vondrák et al, ; Vondrák & Malíček, ), Tatra Mountains in Poland (Wilk, ), Caucasus Mountains in Abkhasia, Murmansk region in Russia, Torne Lappmark in Sweden (Frolov & Konoreva, ) and here it is newly reported from Sierra Nevada in Spain.…”
Section: Taxonomymentioning
confidence: 65%
“…However, the last checklist of li chens of the region with full information about species distribution in the area was published nearly 50 years ago (Dombrovskaya, 1970). In our days most of the publications present lists of rare species and species new for the region or checklists without information about locali ties (Urbanavichus et al, 2008;Urbanavichus, 2014;2015;Frolov & Konoreva, 2016;Konoreva, 2016). There are only two checklists with localities cited for each species -for the Lapland Biosphere Reserve and for the Pasvik Nature Reserve (Fadeeva et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…The former species, however, has paler yellow-orange apothecia, and young apothecia usually have a conspicuous ring of thin grey thalline exciple. The pale morphotype of Lendemeriella borealis (see Frolov & Konoreva 2016) also resembles O. infirma; however, it usually has a well-developed whitish areolate thallus and paler, orange-yellow apothecia with a greyish to grey proper exciple containing Cinereorufa-green.…”
Section: Mycobank No: Mb 833718mentioning
confidence: 99%
“…Approximately 18% of this diversity (c. 180 species) is known from Russia (e.g. Urbanavichus 2010; Urbanavichus & Urbanavichene 2012;Vondrák et al 2013bVondrák et al , 2017Vondrák et al , 2019Muchnik et al 2014;Frolov & Konoreva 2016) and it makes the family one of the most species-rich in the country (Urbanavichus 2014). The highest number of species of Teloschistaceae are found in regions characterised by dry and warm rocky steppes with base-rich bedrock, namely Southern European Russia, Russian Caucasus, Southern Ural and Southern Siberia (Urbanavichus 2014).…”
Section: Introductionmentioning
confidence: 99%